Gas Injection for Disposal and Enhanced Recovery. - Wu, Ying (Advances in natural gas engineering., 2014)
This is the fourth volume in a series of books focusing on natural gas engineering, focusing on two of the most important issues facing the industry today: disposal and enhanced recovery of natural gas. This volume includes information for both upstream and downstream operations, including chapters on shale, geological issues, chemical and thermodynamic models, and much more. Written by some of the most well-known and respected chemical and process engineers working with natural gas today, the chapters in this important volume represent the most cutting-edge and state-of-the-art processes.